If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12(3x-2)=56
We move all terms to the left:
12(3x-2)-(56)=0
We multiply parentheses
36x-24-56=0
We add all the numbers together, and all the variables
36x-80=0
We move all terms containing x to the left, all other terms to the right
36x=80
x=80/36
x=2+2/9
| 4m-2=m | | 9x+17=9x+21 | | X-8=30+3x | | x=(2x+45) | | 2*4.6=g | | 8(2x+3)=19 | | 420=(10+x) | | -3x+7=-11-5x | | 12-2×5=r | | 2m+16=6m-4 | | 3(2x−3)=4x−5 | | n-8=2/3 | | 2(x×20)=90 | | w(3w+4)=24 | | 6u=2 | | 6y+10=114 | | 3u+7=-14 | | 12.1+a=8 | | 9x+1=x+6+3x | | 2x+1x=9+9 | | y=49+-84+27 | | X+2=5x-14 | | 9x^2-82x=0 | | 5/8*w=3 | | 0,5x=0 | | c-5.9=1.9 | | X+10=7x-38 | | Mx90=42 | | 6+2.1=c | | C=38.62+0.50x | | 7x+3=-165-7x | | 6(1+4x)=150 |